Modelling of saw structures and design of saw biosensor circuits and devices - Rahul Kishor (2013)
In this thesis, we focus upon the implementation of a biosensor and micropump using surface acoustic wave (SAW) technique. The integrated readout circuit simulation uses the electrical equivalent model for the SAW, designed using ANSYS finite element method (FEM). A micropump module using the SAW streaming effect is designed and fabricated. The two modules forms the most important sub-blocks in developing an acoustic microfluidic platform for diagnostic devices